Effect of Mooring Line Damage on the Responses of Truss Spar Platforms - Montasir, O.A.A; Kurian, V.J.; Mohamed , M.A.W. (2010)
Abstract-The exploration of hydrocarbon reservoirs in ultra deep water requires the use of innovative floating platform configurations. Due to the global climate change, unexpected ocean environments lead to damages on many offshore platforms. This paper addresses the effect of mooring line damages due to the dynamic responses of truss spar platforms in regular waves. The motion responses have been determined using a time-domain simulation. Quasi static analysis of mooring lines has been conducted to obtain the mooring lines stiffness. Wave forces are calculated using Morison’s equation. The numerical results show that missing of mooring lines affect surge motion more than heave and pitch motions.